Prediction of Land Use Change Due to Light Rail Transit (LRT) Development in Palembang - Isro Saputra; F A Nabila (TATALOKA, 2020)
Light rail transit (LRT) is an effective transportation in serving the needs of movement in urban area that can increase commercial land uses. The first construction of LRT in Palembang started in 2015 which became one of the national priority projects in Indonesia. The development had an impact on land use change around the LRT corridor. This paper attempts to identify land use change due to LRT development in Palembang. This study used an explorative approach to develop an understanding of land use change due to the development of LRT and Markov-cellular automata model to predict the change. The results of this study indicated that the prediction of land use change in 2025 around the LRT corridor tends to shift more into commercial land use, this will increase investment from commercial activities in the Palembang LRT Corridor.